Study on Pad Performance Deterioration in Chemical Mechanical Polishing (CMP) of Fused Silica. (1st January 2018) - Zhou, Yan; Luo, Haimei; Pan, Guoshun; Zou, Chunli; Luo, Guihai; Chen, Gaopan; Kang, Chengxi
Abstract : Polishing pad is considered one of the most important factors in chemical mechanical polishing (CMP) toward the material surface fabrication. Here, based on the ultra-smooth surface polishing of fused silica, the variation and deterioration of the pad performance are studied. The variations of the removal rate and polished surface quality of fused silica with the used time of the pad are investigated. Meanwhile, the variations of the pad performance during CMP process are analyzed. Scanning electronic microscope (SEM) is used to observe the physical morphology change of the pad. Attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) is used to evaluate the chemical change of the pad. And the surface roughness and hardness of the new and the used pad are characterized. The results indicate that with the prolonging of the usage time of the pad, the thickness of the pad becomes reduced and the surface of the pad becomes roughened, resulting in the decrease of removal rate of fused silica and the roughening of the polished surface. The mechanism of the pad performance deterioration is discussed. In addition, the effect of the downward pressure in CMP on the pad performance deterioration is presented.